Traumatic ventricular septal defect resulting in severe pulmonary hypertension - Crompton, Joseph G. (Oxford University Press, 2014)
Traumatic ventricular septal defect (VSD) is a widely-recognized complication of both penetrating and blunt trauma. Most cases are repaired operatively without the long-term complications of pulmonary hypertension and heart failure that are associated with unrepaired congenital VSD in the pediatric population. To our knowledge, this is the first case report of a patient with a traumatic VSD who declined surgical repair at the time of injury and subsequently developed long-term complications of pulmonary hypertension and heart failure. With nearly 20 years of follow-up, this case demonstrates that the absence of surgical treatment in asymptomatic adult patients at the time of injury can lead to long-term complications associated with VSD. This case also shows that aggressive surgical treatment in patients with severe pulmonary vascular disease and heart failure secondary to traumatic VSD can be performed safely and should be considered in cases refractory to efficacious medical interventions.